Clinical characteristics of monkeypox virus infections among men with and without HIV: A large outbreak cohort in Germany. Issue 4 (4th September 2022) - Hoffmann, Christian; Jessen, Heiko; Wyen, Christoph; Grunwald, Stephan; Noe, Sebastian; Teichmann, Jörn; Krauss, Anja‐Sophie; Kolarikal, Henning; Scholten, Stefan; Schuler, Christoph; Bickel, Markus; Roll, Clemens; et al.
Abstract: Background: Since May 2022, increasing numbers of monkeypox virus (MPXV) infections have been reported from across Europe and North America. Studies, mainly from Africa, have suggested a higher risk for severe MPXV cases in people living with HIV. Methods: This was a retrospective study of all confirmed MPXV infections observed in the participating centres since 19 May 2022. We conducted a chart review to evaluate clinical characteristics, comorbidities, and coinfections, including HIV, viral hepatitis, and sexually transmitted infections (STIs). Results: By 30 June 2022, a total of 546 MPXV infections were reported from 42 German centres. All patients were men who have sex with men (MSM), of whom 256 (46.9%) were living with HIV, mostly with a preserved immune system and with viral suppression. In total, 232 (42.5%) MSM were also taking HIV pre‐exposure prophylaxis (PrEP) and 58 (10.6%) MSM had no known HIV infection or PrEP use. The median age was 39 years (range 20–67), and comorbidities were rare. However, 52.4% and 29.4% of all patients had been diagnosed with at least one STI within the last 6 months or within the last 4 weeks, respectively. The most frequent localizations of MPXV infection were genital (49.9%) and anal (47.9%), whereas fever (53.2%) and lymphadenopathy (42.6%) were the most frequent general symptoms. The hospitalization rate was low (4.0%), and no fatal course was observed. The clinical picture showed no apparent differences between MSM with or without HIV. Conclusions: In this preliminary cohort analysis from a current large outbreak among MSM in Germany, the clinical picture of MPXV infection did not differ between MSM with and without HIV infection. Severe courses were rare and hospitalization rates were low. However, most patients were relatively healthy, and only a few people living with HIV were viremic or severely immunosuppressed.